PENERAPAN TGT (TEAM GAMES TOURNAMENT) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI KELAS X TEKNIK INSTALASI TENAGA LISTRIK SMKN 2 SIGLI - Zulfa Setiawan; Hari Anna Lastya; Sadrina Sadrina (JPTE FT UNY, 2021)
ABSTRACT:This research is conducted because of the lack of creative and innovative learning models in the vocational school. However, the research aims were to analyze the effect of the team games tournament learning model on student achievement on electronic basic. The research used a quantitative method and quasi-experimental approach with a one-group pretest-posttest design. The instrument used were test paper and questionnaires. Data collected in this study passed through pretest, posttest, and questionnaires. The data is processed using the t-test. The results show differences in student learning outcomes between before and after the implementation of this model. This can be seen from the average value of student learning outcomes achieved at pretest posttest (58 76). Hypothesis testing using t-test shows the results of data analysis t count t table (3,665 1.75) so that the working hypothesis (Ha) is accepted. This indicates that the application of TGT in the basic electronics subjects proved could improve the learning outcomes of class X TITL SMKN 2 Sigli students. The results of the questionnaire present that the TGT learning model obtained a very agreeable value. It could conclude that students perceived the TGT learning model as an attractive learning process and effectively improve their motivation in learning Basic Electronics subject matter.ABSTRAK:Penelitian ini dilakukan karena kurangnya model pembelajaran yang kreatif dan inovatif di SMK. Namun penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran turnamen team games terhadap prestasi belajar siswa pada dasar elektronika. Penelitian ini menggunakan metode kuantitatif dan pendekatan eksperimen semu dengan desain one-group pretest-posttest design. Instrumen yang digunakan adalah kertas tes dan angket. Data yang dikumpulkan dalam penelitian ini melalui pretest, posttest, dan angket. Pengolahan data menggunakan uji-t. Hasil penelitian menunjukkan adanya perbedaan hasil belajar siswa antara sebelum dan sesudah penerapan model ini. Hal ini terlihat dari nilai rata-rata hasil belajar siswa yang dicapai pada saat pretest posttest (58 76). Pengujian hipotesis menggunakan uji-t menunjukkan hasil analisis data t hitung t tabel (3,665 1,75) sehingga hipotesis kerja (Ha) diterima. Hal ini menunjukkan bahwa penerapan TGT pada mata pelajaran elektronika dasar terbukti dapat meningkatkan hasil belajar siswa kelas X TITL SMKN 2 Sigli. Hasil angket menunjukkan bahwa model pembelajaran TGT memperoleh nilai sangat setuju. Dapat disimpulkan bahwa model pembelajaran TGT dirasakan siswa sebagai proses pembelajaran yang menarik dan efektif meningkatkan motivasi belajar materi pelajaran Elektronika Dasar.